2012
DOI: 10.1103/physrevb.85.214516
|View full text |Cite
|
Sign up to set email alerts
|

Polarized neutron scattering studies of magnetic excitations in electron-overdoped superconducting BaFe1.85Ni0.15As

Abstract: We use polarized inelastic neutron scattering to study low-energy spin excitations and their spatial anisotropy in electron-overdoped superconducting BaFe1.85Ni0.15As2 (Tc = 14 K). In the normal state, the imaginary part of the dynamic susceptibility, χ ′′ (Q, ω), at the antiferromagnetic (AF) wave vector Q = (0.5, 0.5, 1) increases linearly with energy for E ≤ 13 meV. Upon entering the superconducting state, a spin gap opens below E ≈ 3 meV and a broad neutron spin resonance appears at E ≈ 7 meV. Our careful … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…7. In one extreme, there is FeSe with the resonance entirely anisotropic (although it is unclear at what energy fluctuations become isotropic), and in the other extreme the resonance is fully isotropic as found in overdoped iron pnictides [39,42]. In most systems reported so far, M y M z is observed; namely c-or a-axis (in-plane longitudinal direction at the stripe vector) polarized excitations are at least as intense as b-axis (in-plane transverse direction at the stripe vector) polarized excitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7. In one extreme, there is FeSe with the resonance entirely anisotropic (although it is unclear at what energy fluctuations become isotropic), and in the other extreme the resonance is fully isotropic as found in overdoped iron pnictides [39,42]. In most systems reported so far, M y M z is observed; namely c-or a-axis (in-plane longitudinal direction at the stripe vector) polarized excitations are at least as intense as b-axis (in-plane transverse direction at the stripe vector) polarized excitations.…”
Section: Discussionmentioning
confidence: 99%
“…Spin anisotropy is manifested in the resonance mode of superconducting iron pnictides up to the optimally or slightly overdoped regime in electron-and hole-doped BaFe 2 As 2 [36][37][38], leading to resonance modes that exhibit an anisotropic part in addition to an isotropic part in spin space. The resonance mode becomes fully isotropic well into the overdoped regime [39]. With unpolarized neutron scattering the two parts are difficult to resolve, and it has been suggested that the two parts may have different origins [40].…”
Section: Introductionmentioning
confidence: 99%
“…In this notation, the vector Q in three-dimensional reciprocal space inÅ −1 is defined as Q = Ha scattering 23 . Figure 1 shows energy scans above and below T c at wave vectors Q = (0.5, 0.5, 0) and (0.5, 0.5, 2).…”
Section: Itymentioning
confidence: 99%
“…On this point, it is important to keep in mind that the magnetic anisotropy in these materials is not universal: neutron scattering studies suggest that in LaFeAsO, SrFe 2 As 2 and BaFe 2 As 2 the spins are aligned in-plane [1], but in NdFeAsO [21] along c. In the latter case the spin flop may be masked by spin-reorientation transitions in the Nd subsystem. Additionally, there is evidence in polarized neutron scattering measurements that the anisotropy of low-energy spin fluctuations [22] in electron-doped Ba(Fe 1−x Ni x ) 2 As 2 does not reflect the easy axis of the ordered phase.…”
Section: Figmentioning
confidence: 99%